Forced migrations of Georgia and Ukraine: reasons for the emergence, process features, implications for countries - Elizbarashvili, Nodar; Niemets, Liudmyla Mykolaivna; Meladze, Giorgi; Sehida, Kateryna Yuriivna; Lohvynova, Maryna Oleksandrivna; Meladze, Maia; Sidamonidze, David (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2020)
The purpose of this paper is to analyze the causes, current realities and consequences of forced migrations of Georgia and Ukraine in order to identify key strategies for resolving the socio-economic problems of internally displaced persons and transforming them from a “problem vulnerable group” into an indicator of socio-economic development of the countries.Methodology. The study was conducted using a set of multidisciplinary approaches and methods. The paper was used philosophical, general scientific and concrete scientific research methods. Among them: methods of analysis and synthesis, comparative geographical method, mathematical and statistical, graphical method, problem method and some others.Results. Forced migration in Georgia and Ukraine is associated with armed conflicts, which were supported by the separatist sentiments of the part of the population. The center of the military confrontation in Georgia in 1989-1992 was the Tskhinvali region (South Ossetia), and in 1992-1993 – Abkhazia. In 2008, an armed conflict arose between Georgia, Russia and the separatist groups of South Ossetia, referred to as the Russian-Georgian war. In 2014, the Donbass (Donetsk and Luhansk regions) became a center of hostilities in Ukraine. Because of such military conflicts, millions of people have become internally displaced persons – a socially vulnerable category of the population.Analysis of the structural features of the IDPs of Georgia and Ukraine shows the unevenness of their territorial distribution: IDPs are settled in large cities close to their previous homes and almost completely ignore the countryside. Such resettlement speaks about possible intentions to return to their previous places of residence. As a result of the displacement of IDPs, a large burden on the social and economic spheres is observed in parts of Donetsk and Luhansk, as well as Kharkiv regions, the city of Kiev. A similar picture is observed in Georgia: IDPs are settled closer to the occupied regions of Abkhazia and the Tskhinvali region, in large cities and districts of Tbilisi, Samegrelo-Zemo, Svaneti and Imereti.IDPs have become a real challenge for both countries, with which the government could not finally cope. Unresolved in both countries are the housing problems of IDPs. In Ukraine, in addition to the housing problem, IDPs face acute problems with determining their status, social benefits, and employment. Ignoring the solution of these problems leads to increased tension in society, conflicts at the local level between the migrants and the local population, and, as a consequence, to repeated internal displacement. Resolving the problems of forced migrants should be the first line of policy with IDPs.Scientific novelty. a comprehensive comparative analysis of forced migration of Georgia and Ukraine related to military conflicts in the paper was carried out for the first time. The methodology of human-geographical research of migration processes, in particular forced migration, has been improved. The application of the joint experience of Georgia and Ukraine in solving the problems of IDPs was further developed.Practical significance. Studying the joint experience of countries in solving the socio-economic problems of IDPs, the features of their integration and adaptation will contribute to a deeper analysis of these processes at all levels of territorial organization, ensuring the erasing of borders between such a category as "migrants" and "ordinary population". This paper is only a part of the comprehensive study of the problems of IDPs, so the next step will be a study of the features of IDP integration in the host communities of Georgia and the implementation of this experience for Ukraine.